2014
DOI: 10.1128/jcm.01563-14
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Calves Persistently Infected with HoBi-Like Pestivirus and Comparison of Methods for Detection of These Persistent Infections

Abstract: The identification and elimination of persistently infected (PI) cattle are the most effective measures for controlling bovine pestiviruses, including bovine viral diarrhea virus (BVDV) and the emerging HoBi-like viruses. Here, colostrum-deprived calves persistently infected with HoBi-like pestivirus (HoBi-like PI calves) were generated and sampled (serum, buffy coat, and ear notches) on the day of birth (DOB) and weekly for 5 consecutive weeks. The samples were subjected to diagnostic tests for BVDV-two rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…The present study suggests that HoBi‐like pestivirus introduction into a cattle herd has the same outcome as the other, more widespread, pestiviruses, BVDV‐1 and BVDV‐2, whose impact on animal productivity is well recognized. Recent studies have shown that, analogous to extant pestiviruses, HoBi‐like strains can cause respiratory distress (Decaro et al., , , ), reproductive failures (Cortez et al., ; Decaro et al., ), generation of PI animals (Bauermann et al., ; Decaro et al., ), occurrence of mucosal disease (Decaro et al., ; Weber et al., ), severely affecting the productive performances of the cattle industry. In the outbreak described in the present report, the virus re‐emerged 4 years after its first detection in 2010, causing both reproductive and enteric disease.…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggests that HoBi‐like pestivirus introduction into a cattle herd has the same outcome as the other, more widespread, pestiviruses, BVDV‐1 and BVDV‐2, whose impact on animal productivity is well recognized. Recent studies have shown that, analogous to extant pestiviruses, HoBi‐like strains can cause respiratory distress (Decaro et al., , , ), reproductive failures (Cortez et al., ; Decaro et al., ), generation of PI animals (Bauermann et al., ; Decaro et al., ), occurrence of mucosal disease (Decaro et al., ; Weber et al., ), severely affecting the productive performances of the cattle industry. In the outbreak described in the present report, the virus re‐emerged 4 years after its first detection in 2010, causing both reproductive and enteric disease.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on HoBilike pestivirus infections and related diseases are progressively increasing (Cortez et al, 2006;Kampa et al, 2010;Decaro et al, 2011Decaro et al, , 2012aDecaro et al, ,c, 2013aDecaro et al, , 2014Weber et al, 2014;Haider et al, 2014;Mishra et al, 2014), and it is not clear if the existing diagnostic assays are able to detect efficiently this emerging group of pestiviruses (Schirrmeier et al, 2004;Decaro et al, 2010). Although there are several molecular methods for diagnosis of pestivirus infection (Bhudevi and Weinstock, 2003;Young et al, 2006;La Rocca and Sandvik, 2009;Yan et al, 2011;Fan et al, 2012;Zhang et al, 2014), only some assays have been demonstrated to be able to detect HoBi-like pestiviruses (Bauermann et al, 2013(Bauermann et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…A real-time RT-PCR assay for specific detection of HoBi-like viruses has been developed in recent years, but this assay does not detect simultaneously BVDV-1 and BVDV-2 and cross-reaction may occur for high-titer BVDV-2 samples (Decaro et al, 2012b(Decaro et al, , 2013b. In addition, two commercially available real-time RT-PCR assays proved to detect HoBi-like viruses, but with different efficiency on the basis of the sample typology (Bauermann et al, 2014). In this study, to overcome the limitations of the existing methods, a pan-pestivirus TaqMan assay was developed for sensitive detection of bovine pestiviruses, including the novel HoBi-like viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The natural infection with a HoBi‐like pestivirus was first found in aborted foetuses in Brazil and laterly identified in cow serum through epidemiology investigation in Thailand (Stalder et al., ; Stahl et al., ), Decaro et al. reported that the infection is associated with overt disease (respiratory distress and abortion) first in Italy (Decaro et al., , , ), In addition, this emerging virus was reported to cause persistent infection and occurrence of mucosal disease (Decaro et al., , ; Bauermann et al., ). The first CP‐strain of HoBi‐like pestivirus was isolated from a dead heifer's lung after displaying respiratory disease in Italy (Decaro et al., ).…”
Section: Introductionmentioning
confidence: 99%